Combining Lightweight Deep Learning Models with Data Augmentation for Analysis of Cervical Cells - Le, Thi Thu Nga (Springer Nature, 2025)
Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering ((LNICST,volume 649)); International Conference on Smart Objects and Technologies for Social Good; pp: 173-182.